Justification for Head Computed Tomography in Pediatric Patients in a Tertiary Hospital in Jeddah, Saudi Arabia - Khafaji, Mawya A.; Nasr, Ranim Y. (Journal of King Abdulaziz University: Medical Sciences, 2023)
Imaging justification considers the risk–benefit ratio to avoid unnecessary radiation exposure. The use of high-radiationdose imaging modalities, including computed tomography, has increased. In Saudi Arabia, no clear guidelines exist for protecting pediatric patients from unnecessary exposure to ionizing radiation. We aimed to investigate the frequency of unjustified head computed tomography scans among pediatric patients at our hospital. In this study, we enrolled pediatric patients (0–14 years old) who underwent head computed tomography scans between September 2015 and September 2017, and evaluated the frequency of unjustified scans. Among the 1,109 scans, 40.6% (n = 450) had no findings; of these, 68.4% (n = 308) were justified and 31.6% (n = 142) were not. The majority of “no finding” cases were from the emergency department; (285 [63.3%]) and were from patients >5 years old (203 [45.1%]). Thirty percent of “no findings” cases from the emergency department were not justified and 19% were incompatible with the modality. Approximately 40% of cases from the outpatient departments were neither justified nor compatible with this modality. Our findings highlight the need for regular auditing to justify scan requests and a clinical decision system for medical imaging using ionizing radiation